Effects of a new continuous nursing program on the short-term and long-term low back pain in patients after UBED: a retrospective study based on 282 patients - Li, Jucai; Song, Yanli; Wu, Lumei; Su, Dan; Wang, Lin-Feng (Frontiers in Surgery, 2024)
Background Unilateral biportal endoscopic discectomy (UBED) is a widely accepted minimally invasive surgery for the treatment of lumbar degenerative diseases. However, some patients continue to have persistent low back pain (LBP) symptoms in the short and long term after surgery, which may be related to improper postoperative nursing and rehabilitation of patients. Further research is needed to determine whether continuous nursing can improve the symptoms of patients after UBED. Methods This study retrospectively enrolled 282 lumbar disc herniation (LDH) patients who underwent UBED in our hospital from January 2019 to January 2022. The patients were divided into two groups according to whether they accepted the continuous nursing program: 147 patients in the traditional nursing group and 135 patients in the continuous nursing group. Demographic characteristics, radiological parameters, and follow-up data of the patients were collected. Finally, the risk factors of LBP after UBED were analyzed. Results The visual analog scale (VAS) score of LBP in the continuous nursing group was 0.97 ± 1.159 at 3 months and 0.61 ± 0.954 at 12 months after operation, and VAS of leg pain was 0.23 ± 0.421 at 12 months after operation, which were better than those in the traditional nursing group (1.51 ± 1.313, 1.10 ± 1.076, 0.68 ± 0.788, respectively, p < 0.001) The Oswestry disability index (ODI) score of the continuous nursing group was lower than that of the traditional nursing group at 12 months after operation (7.36 ± 6.526 vs. 12.43 ± 6.942, p < 0.001). The rehabilitation completion (7.98 ± 1.857), efficacy satisfaction (9.13 ± 1.101), and re-herniation worry scores (1.97 ± 1.217) in the continuous nursing group were better than those in the traditional nursing group (4.14 ± 3.066, 8.28 ± 1.240, 2.79 ± 1.973, respectively, P < 0.001). The re-herniation rate within 1 year was similar between the two groups (3/135 vs. 2/147, p = 0.673). No incision infection occurred. Multivariate regression analysis showed that risk factors for persistent LBP at 3-month follow-up were degenerative disc [odds ratio (OR): 2.144, CI: 1.306–3.519, p = 0.03], Pfirrmann grade (OR: 3.073, CI: 1.427–6.614, p = 0.04), and surgical time (OR: 0.969, CI: 0.937–1.003, p = 0.74). At the 12-month follow-up, the risk factors for persistent LBP were preoperative VAS of the legs (OR: 1.261, CI: 1.000–1.591, p = 0.05) and Pfirrmann grade (OR: 3.309, CI: 1.460–7.496, p = 0.04). Conclusion Continuous nursing programs can improve the symptoms of short-term and long-term persistent LBP in patients after UBED, enhance the completion of rehabilitation training after UBED, alleviate patients' concerns about recurrence, and improve patients' satisfaction.